Child sex ratio - declining trend: Reasons and consequences - George, Neethu; Britto, Rock; Abhinaya, R; Archana, M; Aruna, A S; Narayan, M Ashwin (Indian Journal of Child Health, 2021)
Child sex ratio (CSR) and over all sex ratio have found to be the important indicator to examine the social commitment against female child. According to census 2011, CSR has been decreased from 927 to 919 in 2011. Many researchers have reported that the sex ratio at birth is in favor of males and the low sex ratio is found to be due to the sex selection strategies of the parents. Despite the higher mortality preponderance for male child, the females were having a decreased ratio during childhood years. Gender discrimination and female infanticide have found to be the important factor responsible for the low CSR. This article tries to shed light into the issue among the states of India, giving a special attention to the state of Tamil Nadu and proposes few remedial measures.